Using mobile location data in biomedical research while preserving privacy. (7th June 2018) - Goldenholz, Daniel M; Goldenholz, Shira R; Krishnamurthy, Kaarkuzhali B; Halamka, John; Karp, Barbara; Tyburski, Matthew; Wendler, David; Moss, Robert; Preston, Kenzie L; Theodore, William
Abstract: Location data are becoming easier to obtain and are now bundled with other metadata in a variety of biomedical research applications. At the same time, the level of sophistication required to protect patient privacy is also increasing. In this article, we provide guidance for institutional review boards (IRBs) to make informed decisions about privacy protections in protocols involving location data. We provide an overview of some of the major categories of technical algorithms and medical–legal tools at the disposal of investigators, as well as the shortcomings of each. Although there is no "one size fits all" approach to privacy protection, this article attempts to describe a set of practical considerations that can be used by investigators, journal editors, and IRBs.